Analysis of the Implementation of Bridge Construction Project Risk Management - Andrian Firdaus Yusuf Al Qordhowi (Institute of Computer Science (IOCS), 2021)
This study aims to analyze the implementation of risk management for bridge construction projects. This research is constructing a bridge in the Gayungan sub-district, Surabaya. This research uses qualitative research with a descriptive analysis approach. The types of data used in this research are primary and secondary data. The direct data collection technique uses a questionnaire technique regarding risk research to collect two opinions: the opportunities and consequences of risk. The method used is expert sampling, namely determining samples known to have experience or expertise in a field. Meanwhile, secondary data collection uses literature study techniques following the research object. Based on the results of the data and analysis, it can be concluded that the risks identified from the respondents' answers are: 18% unacceptable, 58% not expected, 17% acceptable, and 7% ignored. The handling of risks that are classified as extreme risk and high risk based on the largest source of trouble, namely by contractors with more emphasis on project implementation planning and choosing the correct method according to the situation and field conditions, as well as implementing work safety programs to create safe and safe working conditions minimize accidents in the workplace.